'Immersed in Art': Engaged learning in art and design history. (1st June 2021) - Chandler, Lisa; Ward, Alistair; Ward, Lisa
Established approaches to art history pedagogy typically involve a primarily passive form of instruction incorporating the viewing of works projected on screens. While such approaches can convey valuable information, they can also contribute to student disengagement and do not necessarily support deep learning. This article examines three learning initiatives incorporating an immersive teaching space to determine how these forms of technology-enhanced active learning might enhance student comprehension and engagement. The article considers how learning design incorporating the affordances of such immersive environments can provide multimodal learning experiences that stimulate student imaginations and support learning and engagement in a manner that complements rather than replaces traditional modes of instruction.